Deskripsi Minat Belajar Mahasiswa Melalui Tutorial Webinar pada Mata Kuliah Konsep Dasar IPA di SD - Zakirman Zakirman (SAP (Susunan Artikel Pendidikan), 2023)
The basic concept of science in elementary school is one of the subjects in the UT PGSD study program. Universitas Terbuka is a state university in Indonesia that implements Open and Distance Higher Education (PTTJJ) both online and face-to-face. The Covid-19 outbreak that hit our country has an impact on the implementation of online learning as a whole. The webinar tutorial (tuweb) is an alternative to online learning. However, tuweb is still new for students who have been studying face-to-face so that it has an impact on their interest in learning. Therefore, it is important to conduct research in this regard. The purpose of this study was to describe students' interest in learning basic science concepts in elementary schools through webinar tutorials using Microsoft Teams. Microsoft Teams was chosen as a learning media that can support the implementation of tuweb. In this study, the data instruments used were observation sheets and interviews with descriptive data analysis methods. The observation sheet contains indicators of interest in learning namely; a) feelings of pleasure, b) involvement, c) interest and d) concern. The results of the study showed that overall the average percentage of student learning interest on the tuweb for basic science concepts was an indicator of feeling happy 76.75%, an indicator of involvement 78.23%, an indicator of interest 80%, an indicator of attention 79.85%. This indicates that the use of Tuweb provides space for students to interact so that students' interest in learning becomes better.